The effect of inhaled hypertonic saline on lung structure in children aged 3–6 years with cystic fibrosis (SHIP-CT): a multicentre, randomised, double-blind, controlled trial. Issue 7 (July 2022) - Tiddens, Harm A W M; Chen, Yuxin; Andrinopoulou, Eleni-Rosalina; Davis, Stephanie D; Rosenfeld, Margaret; Ratjen, Felix; Kronmal, Richard A; Hinckley Stukovsky, Karen D; Dasiewicz, Alison; Stick, Stephen Michael; ,; Andrinopoulou, Eleni-Rosalina; et al.
Summary: Background: In the Saline Hypertonic in Preschoolers (SHIP) study, inhaled 7% hypertonic saline improved the lung clearance index in children aged 3–6 years with cystic fibrosis, but it remained unclear whether improvement is also seen in structural lung disease. We aimed to assess the effect of inhaled hypertonic saline on chest CT imaging in children aged 3–6 years with cystic fibrosis. Methods: Children with cystic fibrosis were enrolled in this multicentre, randomised, double-blind, controlled study at 23 cystic fibrosis centres in Spain, Denmark, the Netherlands, Italy, France, Belgium, the USA, Canada, and Australia. Eligible participants were children aged 3–6 years who were able to cooperate with chest CT imaging and comply with daily nebuliser treatment. Participants were randomly assigned 1:1 to receive inhaled 2 puffs of 100 μg salbutamol followed by 4mL of either 7% hypertonic saline or 0·9% isotonic saline twice per day for 48 weeks. Randomisation was stratified by age in North America and Australia, and by age and country in Europe. Chest CTs were obtained at baseline and 48 weeks and scored using the Perth-Rotterdam Annotated Grid Morphometric Analysis for Cystic Fibrosis (PRAGMA-CF) method. The primary outcome was the difference between groups in the percentage of total lung volume occupied by abnormal airways (PRAGMA-CF %Disease) measured by chest CT at 48 weeks. Analysis was by intention-to-treat. This study is registered with Clinicaltrials.gov, NCT02950883 . Findings: Between May 24, 2016, and Dec 18, 2019, 134 children were assessed for inclusion. 18 patients were excluded (nine had incomplete or unsuccessful chest CT at enrolment visit, two could not comply with CT training, two had acute respiratory infection, two withdrew consent, two for reasons unknown, and one was already on hypertonic saline). 116 participants were enrolled and randomly assigned to hypertonic saline (n=56) or isotonic saline (n=60). 12 patients dropped out of the study (seven in the hypertonic saline group and five in the isotonic saline group). Mean PRAGMA-CF %Disease at 48 weeks was 0·88% (95% CI 0·60–1·16) in the hypertonic saline group and 1·55% (1·25–1·84) in the isotonic saline group (mean difference 0·67%, 95% CI 0·26–1·08; p=0·0092) based on a linear regression model adjusted for baseline %Disease values and baseline age. Most adverse events in both groups were rated as mild, and the most common adverse event in both groups was cough. Interpretation: Inhaled hypertonic saline for 48 weeks had a positive effect on structural lung changes in children aged 3–6 years with cystic fibrosis relative to isotonic saline. This is the first demonstration of an intervention that alters structural lung disease in children aged 3–6 years with cystic fibrosis. Funding: Cystic Fibrosis Foundation.